Study on genetic diversity in Morinda officinalis F. C. How populations in Quang Ninh using issr marker - Hieu, Hoang Dang; Thu Ha, Chu Thi; Ngoc, Pham Bich; Nhan, Lam Dai; Thuy Huong, Nguyen Thi; Ha, Chu Hoang (Academia Journal of Biology, 2016)
Morinda officinalis F. C. How is a precious medicinal plant, which has been widely used for enhancing immune system and especially increasing men’s physiological health. Because of various tremendous effects, the demand of M. officinalis has increased, recently. In addition, the dwindling of living environments directly resulted in the decline of M. officinalis populations in the nature. Consequently, this caused the significant decrease of M. officinalis’ genetic diversity. In this research, 10 ISSR primers were used to evaluate the genetic diversity of 39 samples gathered at Quang Ninh. The results showed that six among 10 primers could be use for evaluation the diversity of Morinda officinalis population. Forty five fragments of 46 amplified fragments were polymorphism. The phylogenic tree constructed by NTSYS PC 2.1 based on the Jaccard’s genetic coefficient using the algorithm UPGMA showed two major groups ranged from 0.31 to 0.88. The result revealed the value of Nei’s genetic differentiation index (GST) and the estimated gene flow (Nm), which were about 0,3281and 1.0240, respectively. These results demonstrated the diversity at the molecular level of M. officinali F. C. How population distributing in Quang Ninh. These achievements can contribute to the properly sample collection for conservation, breeding or further research on Morinda officinalis F. C. How.